Multimodal imaging analysis of an orthotopic head and neck cancer mouse model and application of anti‐CD137 tumor immune therapy. Issue 4 (16th June 2015) - Vahle, Anne‐Kristin; Hermann, Sven; Schäfers, Michael; Wildner, Michael; Kerem, Alexander; Öztürk, Ender; Jure–Kunkel, Maria; Franklin, Cindy; Lang, Stephan; Brandau, Sven
Abstract: Background: Recent technical progress makes sophisticated noninvasive imaging methods available for murine models. For the first time, in this study, we applied fluorodeoxyglucose (FDG)‐positron emission tomography (PET)‐CT and FDG‐PET‐MRI to a murine orthotopic model of head and neck cancer immunotherapy. Methods: Tumor growth of floor of the mouth tumors was evaluated by multimodal small‐animal imaging using FDG‐PET‐CT and FDG‐PET‐MRI. The immunotherapeutic effects of anti‐CD137 antibody therapy were examined on body weight, tumor growth, and tumor‐infiltrating immune cells in longitudinal imaging studies and immunohistochemical analyses. Results: Imaging revealed aggressive, fast‐growing tumors without evidence of local or distant metastases. CD137 immunotherapy decreased tumor take and growth and stabilized body weight over time. A clear case of tumor regression was demonstrated by longitudinal PET‐CT. Conclusion: The murine model mimics the characteristics of head and neck cancer in humans and offers excellent opportunities to investigate immunomodulatory anticancer drugs. The CD137 antibody showed antitumor effects in some therapy‐responsive mice. © 2015 Wiley Periodicals, Inc. Head Neck 38: 542–549, 2016